‘I never thought that this baby would survive; I thought that it would die any time’: perceptions and care for preterm babies in eastern Uganda - Waiswa, Peter; Nyanzi, Stella; Namusoko-Kalungi, Sarah; Peterson, Stefan; Tomson, Goran; Pariyo, George W. (Tropical medicine & international health, 2010)
To explore the current care for and perceptions about preterm babies among community members in eastern Uganda. methods A neonatal midwife observed care of preterm babies in one general hospital and 15 health centres using a checklist and a field diary. In-depth interviews were conducted with 11 community health workers (CHWs) and also with 10 mothers, six fathers and three grandmothers of preterm babies. Three focus group discussions were conducted with midwives and women and men in the community. Content analysis of data was performed. results Community members mentioned many features which may correctly be used to identify preterm babies. Care practices for preterm babies at health facilities and community level were inadequate and potentially harmful. Health facilities lacked capacity for care of preterm babies in terms of protocols, health workers’ skills, basic equipment, drugs and other supplies. However, community members and CHWs stated that they accepted the introduction of preterm care practices such as skinto- skin and kangaroo mother care. conclusion In this setting, care for preterm babies is inadequate at both health facility and community level. However, acceptance of the recommended newborn care practices indicated by the community is a window of opportunity for introducing programmes for preterm babies. In doing so, consideration needs to be given to the care provided at health facilities as well as to the gaps in community care that are largely influenced by beliefs, perceptions and lack of awareness.
Keywords: preterm; newborn; health facility care; Uganda; newborn care practices; community health workers